Redefining metabolic syndrome as a fat storage condition based on studies of comparative physiology12. (25th May 2013) - Johnson, Richard J.; Stenvinkel, Peter; Martin, Sandra L.; Jani, Alkesh; Sánchez‐Lozada, Laura Gabriela; Hill, James O.; Lanaspa, Miguel A.
Abstract Objective: The metabolic syndrome refers to a constellation of signs including abdominal obesity, elevated serum triglycerides, low HDL‐cholesterol, elevated blood pressure, and insulin resistance. Today approximately one third of the adult population has the metabolic syndrome. While there is little doubt that the signs constituting the metabolic syndrome frequently cluster, much controversy exists over the definition, pathogenesis, or clinical utility. Design and Methods: Here we present evidence from the field of comparative physiology that the metabolic syndrome is similar to the biological process that animals engage to store fat in preparation for periods of food shortage. Results: We propose that the metabolic syndrome be changed to fat storage condition to more clearly align with its etiology. Obesity in humans is likely the consequences of both genetic predisposition (driven in part by thrifty genes) and environment. Recent studies suggest that the loss of the uricase gene may be one factor that predisposes humans to obesity today. Conclusion: Understanding the process animals engage to switch from a lean insulin‐sensitive to an obese insulin‐resistant state may provide novel insights into the cause of obesity and diabetes in humans, and unique opportunities for reversing their pathology.